DEEP ANALYSIS OF POPULIST MOBILIZATION COMPLEXITY WITHIN THE CONTEXT OF INDONESIAN DEMOCRACY: A STUDY ON ELECTORALSTRATEGIES, POLITICAL FIGURES, AND SOCIAL IMPLICATIONS - Ben Brahim S. B.; Sidderatul Akbar; Andika Dirsa; Mohammad Ahmad Bani Amer; Diego Romario De Fretes (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study provides a comprehensive examination of populist mobilization within the intricate landscape of Indonesian democracy. Through a nuanced analysis of electoral strategies, political figures, and social implications, the research delves into the multifaceted nature of populism and its impact on the country's political dynamics. By drawing on a diverse range of scholarly literature and empirical evidence, the study uncovers the historical roots, evolution, and contemporary manifestations of populism in Indonesia. Focusing on electoral strategies, the study investigates the tactics employed by populist movements to mobilize support and shape electoral outcomes. It explores the role of charismatic leadership, emotional appeals, simplified messaging, mass rallies, and social media campaigns in galvanizing public sentiment and garnering political backing. Additionally, the research scrutinizes the profiles of key political figures, such as Joko Widodo and Prabowo Subianto, to elucidate the contrasting leadership styles and policy priorities that define Indonesian populism. Furthermore, the study examines the societal implications of populist mobilization, including its effects on democratic institutions, societal fragmentation, and long-term governance challenges. By analyzing these socio-political impacts, the research contributes to a deeper understanding of the complexities surrounding populist movements in Indonesia and their implications for democratic stability and governance. Ultimately, this study offers valuable insights for policymakers, scholars, and stakeholders seeking to navigate the complex terrain of Indonesian democracy amidst the rise of populist forces.